Annulation chemistry based on tandem Michael addition-enamine formation – An improved method for the preparation of 1-substituted-2, 3, 5, 6, 7, 8-hexahydroquinolin-4(1H)-ones. Issue 43 (24th October 2019) - Glass, Andrew; Higgins, Tyler; Hunt, David A.
Graphical abstract: Highlights: A process to afford 1-substituted-2, 3, 5, 6, 7, 8-hexahydroquinolin-4(1 H )-ones. A tandem Michael addition/enamine formation reaction at room temperature. Reaction times greatly reduced when powdered 4 Å sieves are used. Abstract: The reaction of 2-(but-2-enoyl)cyclohexan-1-one2 with primary amines affords 1-substituted-2, 3, 5, 6, 7, 8-hexahydroquinolin-4(1 H )-ones through a tandem Michael addition/enamine formation reaction sequence at room temperature in high yields. Reaction times are greatly reduced (4–24 h vs. 1–2 h; reflux versus room temperature) when powdered 4 Å sieves are used.